HIV Stigma Scale: Translation and validation of the short version to the Portuguese population - Gonçalves,Mariana (2022)
Abstract The objective was to translate, adapt, and analyze the psychometric properties of a shortened version of the HIV Stigma Scale using a sample of 100 HIV+ adults, with a mean age of 49.88 (SD = 12.03) diagnosed for an average of 9.39 (SD = 7.36) years. The psychometric properties of the short version of the Stigma Scale were analyzed through the one-factor structure and the original four-factor structure, showing good fit for this last model. Convergent validity was found to be close to the acceptable for the factors, “concerns about public attitudes” and “negative self-image”, and good for the factors, “disclosure concerns” and “personalized stigma”. The results showed adequate discriminant validity for all factors, coefficient Omega was above .70 for the four factors, showing adequate reliability. This Portuguese version of the Stigma Scale is a good measure to assess the stigma of people living with HIV.